Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s11357-011-9355-9
|View full text |Cite
|
Sign up to set email alerts
|

Primate aging in the mammalian scheme: the puzzle of extreme variation in brain aging

Abstract: At later ages, humans have high risk of developing Alzheimer disease (AD) which may afflict up to 50% by 90 years. While prosimians and monkeys show more substantial changes, the great apes brains examined show mild neurodegenerative changes. Compared with rodents, primates develop and reproduce slowly and are long lived. The New World primates contain some of the shortest as well as some of the longest-lived monkey species, while the prosimians develop the most rapidly and are the shortest lived. Great apes h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 125 publications
0
56
0
Order By: Relevance
“…45,77,78 Decline in cognitive function in aging humans ranges from mild forgetfulness and slower data processing to severe dementia. Dementia is a syndrome in which thinking skills are impaired to the point that the individual can no longer perform daily functions.…”
Section: Nervous System Disordersmentioning
confidence: 99%
“…45,77,78 Decline in cognitive function in aging humans ranges from mild forgetfulness and slower data processing to severe dementia. Dementia is a syndrome in which thinking skills are impaired to the point that the individual can no longer perform daily functions.…”
Section: Nervous System Disordersmentioning
confidence: 99%
“…Deposits of Aβ protein are apparent with aging in several species, such as non-human primates, dogs, and bears [166][167][168]. Studies of APP transgenic mouse models of AD have shown that there is an abrupt spine loss and neurite dystrophy in the neighborhood of amyloid plaques [169][170][171].…”
Section: Neuronal Impairment In Agingmentioning
confidence: 99%
“…Nonhuman primates are of particular interest for studying the neurobiological correlates of aging because of their close phylogenetic relationship with humans (Finch and Austad, 2012). Nonhuman primates are often used as models to understand the effects of aging independent of the cellular changes that cause age-related neurodegenerative disorders commonly seen in humans such as Alzheimer's disease (Gearing et al, 1996; Kimura et al, 2003; Koo et al, 2012; Lemaitre et al, 2012; Sherwood et al, 2011; Squire et al, 1988).…”
mentioning
confidence: 99%